Conflicting Professional Values in Medical Education - Coulehan, Jack (Cambridge quarterly of healthcare ethics, 2003)
Ten years ago there was little talk about adding “professionalism” to the medical curriculum. Educators seemed to believe that professionalism was like the studs of a building—the occupants assume them to be present, supporting and defining the space in which they live or work, but no one talks much about them. Similarly, educators assumed that professional values would just “happen,” as trainees spent years working with mentors and role models, as had presumably been the case in the past. To continue the metaphor, when educators did discuss ethics and values, they tended to focus more on external building codes than on the nature of construction materials. Building codes are designed to ensure the public's safety by establishing procedures and standards. Likewise, the “new” bioethics of autonomy and informed consent that entered the medical curriculum in the 1970s and 1980s was oriented primarily toward protecting human rights (e.g., protecting patients from clinicians and clinicians from patients) by codification (e.g., who should decide and under what circumstances). In fact, educators explicitly warned students against acting on their personal or professional values in a misguided way—that is, in the absence of adequate ethical constraints, a type of behavior that came to be labeled, pejoratively, as paternalism.